Integral Sustainability as driving force for paradigmatic change in human lifestyle (Sustainability in Debate, 2017)
Since the Rio de Janeiro Earth Summit (synonymous Rio Summit, Rio Conference, or Earth Summit - Portuguese: ECO92), the term sustainability has been used at almost all international meetings and has become a permanent item on the commitment agenda for various entities and corporations. Nevertheless, the concept of sustainability is still an enigma in relation to its limits and magnitude. In this context, the purpose of this scientific article is to present a discussion focused on the inherently multifaceted concept of sustainability. Furthermore, based on the renovation of the meaning and verifying the content fluency, it was noted that a clear systematic concept was lacking. If an ongoing expansion of the content is allowed on one side of this scenario, in contrast to a stagnant concept, on the opposite side, this figurative discussion could cover up problems that society and its representatives want to smooth over rather than deal with them. Therefore, this paper adopts a sustainability concept that makes human aware of their full potential and expand their "inner self". It is the assumption of individual responsibility, based on the understanding to act locally, including social commitment, which comprises human relations, surrounding areas, and, in a broad view, the Planet Earth.